Statistics and probability - Baccay, Elisa S.; Belecina, Rene R. (Sampaloc, Manila : Rex Book Store, Inc., 2022)
"The textbook is meant for the use of Grade 11 students. The content is aligned with the K to 12 Curriculum standards set by the Department of Education. Lessons are organized using the spiral approach assuring that there are no gaps and overlaps from the G10 curriculum and the higher education GEC mathematics subjects. The learning activities are geared toward the development of learning and innovation skills, life and career skills, and knowledge in information processing, media and technology skills as articulated in the P21 Framework for 21st Century Learning. Performance tasks are tiered in addressing higher order thinking skills and are geared toward new careers in the industry. This worktext was written inspired by the tenets of the whole child approach to teaching and learning."
Includes references.
English text.
Keywords: Probabilities and applied mathematics; Probabilities; Statistical mathematics